2004
DOI: 10.1073/pnas.0401301101
|View full text |Cite
|
Sign up to set email alerts
|

A gene cluster for secondary metabolism in oat: Implications for the evolution of metabolic diversity in plants

Abstract: The evolution of the ability to synthesize specialized metabolites is likely to have been key for survival and diversification of different plant species. Oats (Avena spp.) produce antimicrobial triterpenoids (avenacins) that protect against disease. The oat ␤-amyrin synthase gene AsbAS1, which encodes the first committed enzyme in the avenacin biosynthetic pathway, is clearly distinct from other plant ␤-amyrin synthases. Here we show that AsbAS1 has arisen by duplication and divergence of a cycloartenol synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
300
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(312 citation statements)
references
References 52 publications
5
300
0
1
Order By: Relevance
“…An obvious assumption is that these metabolic gene clusters have arisen by horizontal gene transfer from microbes. However there is compelling evidence to indicate this is not the case, and that the clusters are most likely to have been assembled from plant genes by recruitment of genes from elsewhere in the genome through gene duplication, neofunctionalization, and genome reorganization Qi et al, 2004Qi et al, , 2006Field and Osbourn, 2008;Osbourn and Field, 2009;Swaminathan et al, 2009). Thus clustering appears to have occurred de novo through some form of convergent evolutionary process.…”
Section: Operon-like Gene Clusters In Plantsmentioning
confidence: 92%
See 1 more Smart Citation
“…An obvious assumption is that these metabolic gene clusters have arisen by horizontal gene transfer from microbes. However there is compelling evidence to indicate this is not the case, and that the clusters are most likely to have been assembled from plant genes by recruitment of genes from elsewhere in the genome through gene duplication, neofunctionalization, and genome reorganization Qi et al, 2004Qi et al, , 2006Field and Osbourn, 2008;Osbourn and Field, 2009;Swaminathan et al, 2009). Thus clustering appears to have occurred de novo through some form of convergent evolutionary process.…”
Section: Operon-like Gene Clusters In Plantsmentioning
confidence: 92%
“…Unlike operons, the genes within these clusters are transcribed separately. The five plant clusters are for the synthesis of cyclic hydroxamic acids in maize (Frey et al, 1997(Frey et al, , 2003(Frey et al, , 2009von Rad et al, 2001;Jonczyk et al, 2008), triterpenes in oat (Avena sativa) and Arabidopsis (the avenacin and thalianol clusters, respectively; Papadopoulou et al, 1999;Haralampidis et al, 2001;Qi et al, 2004Qi et al, , 2006Field and Osbourn, 2008;Mylona et al, 2008;Mugford et al, 2009), and diterpenes in rice (Oryza sativa; the momilactone and phytocassane clusters; Sakamoto et al, 2004;Wilderman et al, 2004;Shimura et al, 2007;Swaminathan et al, 2009). These clusters are diverse in organization and function and all appear to have evolved independently (Field and Osbourn, 2008;Frey et al, 2009;Osbourn and Field, 2009;Swaminathan et al, 2009).…”
Section: Operon-like Gene Clusters In Plantsmentioning
confidence: 99%
“…5 Such secondary metabolism gene clusters are unusual in plants and generally are taken as an indication of strong selective pressure for production of the resulting compound operating over evolutionarily long timescales. 6 Together these findings suggest OsKSL4 has served as a syn-pimaradiene specific synthase for an extended period of time, with no selective pressure to retain catalytic features in its active site for more complex reaction mechanisms. Accordingly, mutational analysis of OsKSL4 provides an opportunity to investigate the possibility that the previously identified carbocation proximal single residue change acts as a true switch controlling reaction complexity.…”
mentioning
confidence: 88%
“…There is ample evidence that the order of genes along chromosomes in many eukaryotes is nonrandomly distributed (Lee and Sonnhammer 2003;Hurst et al 2004), with similarities to the widespread, sometimes operondriven, prokaryotic segregation of clustered genes that represent a functional unit (Lawrence 2002). A notable example is the complete genetic cosegregation of multiple enzymes in an antimicrobial defense pathway in oat plants (Qi et al 2004). A recent study in yeast revealed that such gene clusters were formed through a set of genomic rearrangements under intense selective pressure (Wong and Wolfe 2005).…”
mentioning
confidence: 99%